Minimum Evaporation Model of Dermatological Delivery Systems. Lamellar Liquid Crystal Formulations Containing Brazilian Nut (Bertholletia excelsa HBK) Vegetable Oil and Guarana Glycolic Extract - Silva, Silas Arandas Monteiro e; Valarini, Michele Fernanda Costa; Chorilli, Marlus; Friberg, Stig E.; Leonardi, Gislaine Ricci (Journal of dispersion science and technology, 2014)
Formulations with lyotropic liquid crystals were prepared from a Brazilian nut vegetable oil, guarana extract and combination of sorbitan monooleate (Span 80) and sorbitan monolaurate ethoxylate EO 20 (Tween 20) in the ratio 1:3 (surfactant component) and their physical-chemical aspects and rheological properties were determined. Compositions with liquid crystals were found in the pseudoternary diagram in a surfactant range of 70-90% and polarized light microscopy, small-angle x-ray scattering (SAXS) showed them to be lamellar. The preparations were furthermore characterized rheologically by shear stress shear rate sweeps finding plastic and pseudoplastic behavior without thixotropy. Electric conductivity and pH measurements demonstrated a potential for future application as dermatological delivery system of the active compounds in the Bertholletia excelsa and Paullinia cupana.